Finite Element Analysis Of Oil and Gas Pipeline Buried In Soil Using Abacus - VINAY N (2011)
INTERNAL GUIDE : Ravikant T EXTERNAL GUIDE:Niranjan P S USN NO : 1MJ10CSE15A CARRIED OUT AT : M V J College Of Engineering Bangalore-67 ACC NO : SE4
Keywords: Finite Element Analysis Of Oil